Preliminary Study on Plate Waste from “Daily Dish” in Restaurants - Miguel Castro; Kamila Soares; Carlos Ribeiro; Alexandra Esteves (Biology and Life Sciences Forum, 2025)
Food waste (FW) is a pressing global challenge, with food service establishments playing a significant role in exacerbating the issue. Efforts to tackle food waste are driven by growing concerns over its far-reaching impacts, including resource depletion, food security risks, and environmental, social, and economic costs. Our study aimed to quantify and analyze plate waste (PW) in three Portuguese restaurants, focusing on waste composition and reduction strategies. Data was collected over 10 days in each restaurant, categorizing waste into carbohydrate-based foods, protein-based foods, and vegetables. Statistical analyses were used to compare waste patterns. Results showed that carbohydrate-based foods, such as rice and potatoes, were the most wasted (16.3% to 21.9% of total waste). Despite serving portions 43% smaller than those in comparable studies, the percentage of PW (10–13%) was similar, indicating higher relative waste. Significant differences were found among food categories (p < 0.05) but not between restaurants or dish types (meat vs. fish). In conclusion, menu optimization and portion control are essential to reduce PW, particularly for less popular dishes. This study highlights the challenges of implementing food waste reduction measures in restaurants and provides insights for aligning with global sustainability goals.